Confucius and Cicero - Balbo, Andrea; Ahn, Jaewon (Roma Sinica, 2020)
This book explores the relationships between ancient Roman and Confucian thought, paying particular attention to their relevance for the contemporary world. More than 10 scholars from all around the world offer thereby a reference work for the comparative research between Roman (and early Greek) and Eastern thought, setting new trends in the panorama of Classical and Comparative Studies.